Suicide attempts by poisoning recorded at a toxicological information and assistance center: a cross-sectional study, Fortaleza, 2022 - Hendyelle Rodrigues Ferreira e Silva; Wanderley Pinheiro de Holanda Júnior; Karla do Nascimento Magalhães; Dário Luis do Nascimento Magalhães; Alan Queiroz de Souza Santos; Maria Augusta Drago Ferreira (Epidemiologia e Serviços de Saúde)
Abstract Objective To outline the epidemiological profile of poisonings due to attempted suicide recorded at a toxicological information and assistance center in Fortaleza, Ceará, Brazil, in 2022. Methods Cross-sectional study with data recorded from January 1st to December 31, 2022. The population included all cases of poisoning due to attempted suicide registered by the center during the period. The data were collected from the Brazilian Poisoning Data System of the Toxicological Information and Assistance Centers. The analysis was based on descriptive statistics, through the calculation of absolute and relative frequencies for each variable. Results 360 cases of attempted suicide were identified, with the main groups of toxic agents being medications (64.4%), pesticides (18.9%) and combinations of agents (10.3%). Most of the cases involved females (61.4%), occurred in urban areas (91.1%), in Fortaleza (65.3%) and in homes (88.0%). The age group of 20-29 years (29.3%) with ‘student’ as the occupation (15.6%) stood out among the records. In 90.3% of cases, there were clinical signs and symptoms, and the oral route was the most used (97.5%); 45.5% required hospitalization; and 79.4% recovered. Pesticides had the highest lethality (8.8%). Conclusion The results showed that suicide attempts by poisoning mainly affect women, occur predominantly at home, and have a favorable clinical outcome. Medications were the most involved toxic agents, and pesticides were the most lethal. These results reinforce the importance of continuous monitoring of cases and the implementation of preventive strategies aimed at the most vulnerable groups.